(untitled) (Hoboken, New Jersey, 2007)
This series provides the most comprehensive and highly focused treatment of important organic reactions currently available. All volumes of Organic Reactions (including this one) are collections of chapters each devoted to a single reaction or a definitive phase of a reaction, of wide applicability.
Keywords: Organic reactions,Phản ứng hữu cơ